Learning in the Merdeka Curriculum: Elementary School Teachers' Understanding of Differentiated Learning - Witraguna, Kadek Yudista; Setiawati, Gusti Ayu Dewi; Wahyuni, Ni Nyoman Tri; Jaya, I Ketut Manik Asta; Mediani, Ni Kadek Ari Anggreni (Universitas Pendidikan Ganesha, 2024)
The Merdeka Curriculum is designed to overcome post-pandemic educational challenges. The Merdeka Curriculum provides students to carry out learning activities freely, which means that they can think independently, innovative, learn autonomously, and be creative. To support The Merdeka Curriculum implementation in teaching, teachers can apply differentiated learning where students can study subjects according to their abilities, preferences, and needs. However, the enthusiasm of teachers in implementing the Merdeka Curriculum is not matched with equitable training on differentiated learning. Therefore, the purpose of this research is to obtain an overview of differentiated learning understanding on elementary school teachers in the context of Merdeka Curriculum. This research is a qualitative descriptive study. The data was collected by administering questionnaires to the principals and teachers from 14 elementary schools. The questionnaires were used to measure elementary school teachers' understanding of differentiated learning, while interviews were conducted to obtain additional information regarding elementary school teachers' comprehension of differentiated learning. The data obtained is then analyzed descriptively. This study revealed that many elementary school teachers do not understand well about differentiated learning due to a lack of training and mentoring. Teachers improve their Merdeka Curriculum and differentiated learning understanding independently through the